Radio IITA farmer’s outreach (Maiden Edition) – Soybean - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
Radio IITA launches the maiden edition of its Farmers’ Outreach project aimed at training farmers on the management and best practices in agriculture, starting with young soybean farmers in its host state, Oyo, in South-West Nigeria.